Developing the Arab Polygamy Anxiety Scale: Content Validity, Factor Analysis, and Reliability - Aldahadha, Basim (Journal of religion and health, 2025)
Islam allows for polygamy under conditions of justice and ability. However, many doubt the ability to engage in polygamy for fear of unexpected and substantially challenging consequences in the future. To help individuals understand themselves, the polygamy anxiety scale (PAS) was developed. This study aimed to collect items referring to the PAS from previous theoretical literature. The items were evaluated by experts (N = 21) and were shortened to 33 items. Two different types of samples were obtained. The first sample (N = 427) was used to verify the validity of the exploratory factor analysis (EFA). The results revealed that four factors explained 71% of the total variance. The items were distributed according to financial, family, physical, and personal factors (28 items). The second sample (N = 389) was used to verify the CFA, convergent validity, and reliability. In addition, four factors were confirmed using CFA. This result was consistent with the standard. Additionally, the results revealed that all correlations between the PAS score and future marriage anxiety, general anxiety, self-esteem and marital adjustment were statistically significant. Cronbach’s alpha values for the four factors ranged between 0.86 and 0.79, and the total score was 0.90. Finally, the correlations between the PAS scores and the four factors were statistically significant. The study concluded that PAS is suitable for Muslims who desire polygamy and can be used to enhance mental health and protect families, children, and wives.